In Uzbek Q Is Weared On Thumb And Finger Jewelry Names - Pardayeva Izzat Kholbo' tayevna (Zien Journals, 2024)
Uzbek in the language to the hand wearable jewelry decoration items two , ie wrist and to the finger wearable decoration from items consists of In our language this jewelry of items from the face more than types there is . This is jewelry decoration items ( ie ring , bracelet and others ) of appear to be long to history go is worn
Keywords: jewelry; jewelry items; ring; bracelet